Perceptions and experiences of individuals at-risk of rheumatoid arthritis (RA) knowing about their risk of developing RA and being offered preventive treatment: systematic review and thematic synthesis of qualitative studies. Issue 2 (8th November 2021) - Siddle, Heidi J; Chapman, Lara S; Mankia, Kulveer; Zăbălan, Codruța; Kouloumas, Marios; Raza, Karim; Falahee, Marie; Kerry, Joel; Kerschbaumer, Andreas; Aletaha, Daniel; Emery, Paul; Richards, Suzanne H
Abstract : Objectives: There is increasing interest in identifying individuals at-risk of rheumatoid arthritis (RA) and initiating early treatment to prevent or delay the onset of arthritis. We aimed to describe the perceptions and experiences of at-risk individuals and to inform the conduct of clinical trials and studies, and clinical practice. Methods: A systematic review and thematic synthesis of qualitative studies was conducted. Two review authors independently screened studies for inclusion, appraised their methodological quality using the Critical Appraisal Skills Programme checklist and assessed confidence in the findings using the Grading of Recommendations Assessment, Development and Evaluation–Confidence in Evidence from Reviews of Qualitative Research approach. Results: Seven studies involving 115 individuals at-risk of developing RA were included. Three major themes (seven subthemes) were identified: understanding the risk of developing RA (knowledge of RA and identification of potential risk factors); preventive interventions to reduce the risk of developing RA (understanding the value and role of preventive interventions, and engagement with preventive interventions); and perceptions of predictive testing for RA (benefits of predictive testing, decision to undertake predictive testing and concerns about predictive testing). Moderate confidence in most review findings was evident. Conclusion: While there are clear benefits in informing individuals at-risk of RA about their risk following predictive testing and offering preventive treatment, there are potential barriers to engagement, intensified by the burden of uncertainty. Identification of the optimum approaches for presenting risk information, including the risks and benefits of engaging with preventive interventions, is urgently needed to support individuals at-risk of RA in their decision making. PROSPERO registration number: CRD42021236034.